Teologi Properti: Telaah Eksistensi dan Fungsi Kekayaan - Ahmad Munir (Universitas Islam Negeri Mataram, 2008)
In the Al-Qur’an, human desire for wealth to meet their needs is viewed as common (thabi‘i) and urgent (dlarûri). Wealth is considered a means for human to be closer to their Creator. In theological perspective, human relation to their fellows and nature is fundamental. The relation is divided into three kinds. First, cooperative relation is the relation between human and their fellows in which every human has the same right to use available natural resources. Second, consumptive relation is the relation between human and nature in which human is an authority for using natural resources and nature is an object. Third, responsible (mustakhlif) relation is the relation between human and their Creator in which human has to be responsible for using natural resources. Based on the relations, wealth for human is expected to be a means of strengthening human characters and leading to the supreme state beside God and human.